Retrospective Analysis of Amraz-e-Anf (Diseases of Nose) Conditions attended to the Out-Patient Department at Unani Ayurvedic Research Hospital, Manchanthoduwai, Sri Lanka - Zahra, A.R.F.; Maheez, M.C.M.; Fazeenah, A.H.A. (Faculty of Indigenous Medicine, University of Colombo, 2025)
Amraz-e-Anf (diseases of the nose) related conditions are common in Sri Lanka and have a significant impact on quality of life. This study aims to conduct a demographic analysis, including the commonly affected age range and the prescribed medications for Amraz-e-Anf conditions such as Nazla-va-Zukam (Common cold), Nazla-e-Haar (Allergic rhinitis), Nazla-e-Barid (Sinusitis), Iltihab-e-Tajafeeful-Anf Muzmin (Chronic sinusitis), and Bawaseer-ul-Anf (Nasal polyps). Survey analysis conducted as a retrospective observational study with a sample size of 336, Outpatient Department via a stratified sampling method. Data were analyzed using descriptive statistical methods via Microsoft Excel 2016. The study revealed that in the numerical data, males (52%) and females (48%) were affected by Amraz-e-Anf. The most frequently treated age group was under 10 years (25%). Among the attended cases, Nazla-vaZukam (78%), Nazla-e-Haar (9%), Nazla-e-Barid (9%), Iltihab-e-Tajafeeful-Anf Muzmin (3%), and Bawaseer-ul-Anf (1%). Notably, the affected age range was 28.15 ± 21.85 years (SD). In the categorical data, 18 drugs were most commonly prescribed, including 4 Unani Drugs: Hab-e-Zeequnnafs, Hab-e-Ayarij, Itriphal-e-Ustakhudus, and Itriphal-e-Muqawwie-Dimagh. The analyzed data showed that males were affected more than females. The most common condition was Nazla-va-Zukam. The most affected mean age range was 6.20 – 43.70 years. 22.22% Unani drugs are identified in categorical data.
Keywords: Amraz-e-Anf; Demographic analysis; Iltihab-e-Tajafeeful-Anf muzmin; Nazla-va-Zukam; Nazla-e-Haar; Nazla-e-Barid; Quality of life